PERAN PAJAK HIBURAN DAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN LEBAK - Friska Lia Imelda; Raden Irna Afriani; Novi Handayani (Gapenas Publisher, 2022)
Sources of regional original income consist of regional tax revenues, regional levies, results of separated regional wealth management and other legitimate regional revenues.. Realization of local revenue decreased in 2019, the realization of entertainment tax decreased in 2020 and 2021, and realization of taxes on non-metallic minerals and rocks decreased in 2019 and 2020. The purpose of this study was to determine the effect of entertainment taxes and taxes on non-metallic minerals and rocks on Lebak Regency's Original Revenue in 2018-2021 partially or simultaneously with the object of research at the Regional Finance and Assets Agency of Lebak Regency. This study uses a quantitative approach. The population in this study is the realization of entertainment tax revenue, non-metallic minerals and rock tax and local revenue for 2018-2021. The research sample obtained by the saturated sampling method amounted to 48 samples The results showed that the entertainment tax variable based on the partial test obtained a value of tcount-0,139 > ttable-2,01410 with a significance value of 0,890 > 0,05. The non-metal mineral tax variable and rock value obtained tcount 2,223 > ttable 2,01410 with a significance value of 0,31 < 0,05. Simultaneous test results obtained Fcount 2,490 < Ftable 3,20 with a significance value of 0,094 > 0,05. The conclusion of this study is that partially entertainment tax has no effect on local revenue and non-metallic mineral and rock taxes have a significant effect on local revenue. Simultaneously entertainment tax and taxes on non-metallic minerals and rocks no effect on local revenue